X-Ray Crystallographic And I-R Studies Of Systemic Fungicide Thiophanate Methyl - DR JYOTSNA CHAUHAN; GARGI BHATTACHARYA (International Journal of Pharma and Bio Sciences, 2012)
The activity of fungicides is intimately related to its chemical structure. Knowledge of the chemical structure is useful for the synthesis of new compounds with more specific actions and fewer adverse reactions, to increase/decrease the duration of action of the original drug or fungicide to get a more potent compound, to restrict the action to a specific system of the body or plant and to reduce the adverse reactions, toxicity and other disadvantages associated. The interactions of fungicides with the macromolecule of the parasite are dependent on the stereochemistry of these compounds. In order to design more effective fungicides, it is necessary to analysis the three dimensional structure of these compounds and if possible the receptor molecule. Recently it has been observed that some of the fungicides are losing their effects. So we can design analogous compounds as a substitute, if their structures are known. A rational approach to test these fungicides is to know the three dimensional structure of these compounds and macromolecular receptor sites.The structures of these compounds can be obtained by X-ray diffraction method in crystalline form and they will invariably be similar to their structure in solutions. The single crystals of Thiophanate Methyl was grown.The Crystal system is Triclinic with space group P-1 and the unit cell parameters obtained are a = 10.191(5) A0, b = 11.203(5)A0, c = 17.151(5) A0, α = 76.909(5) deg., β = 86.051(5) deg., γ = 72.426(5) deg. The composition of crystal Thiophanate methyl is confirmed by infra-red spectra. It has been found that Thiophanate methyl has both the preventive and curative actions and is most active in the thioallophanic acid group. Substitution on benzene ring decreases the fungitoxicity, A CH2 group introduced between the benzimidazole ring and the amino group reduces the antifungal action of the active substance, thus modified. The fungicidal effect decreases with increasing length of alkyl chain.